2015
DOI: 10.1111/jcal.12113
|View full text |Cite
|
Sign up to set email alerts
|

Supporting conceptual understanding of the associative and distributive properties through digital gameplay

Abstract: There has been a steady rise in the support for games as learning environments. This support is largely based on the strong levels of engagement and motivation observed during gameplay. What has proven difficult is the ability to consistently design and develop learning games that are both engaging and educationally viable. Those in the game-based learning community contend the solution is to tightly integrate instructional objective(s) within the game's mechanics. In order to investigate whether or not intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…The two digital games used in this study were carefully selected and recommended to the participating teachers for use in this study as they had been shown to have a positive impact on mathematical learning outcomes in previous empirical studies and employed game mechanics that mapped directly to learning objectives (Denham, ). Ratio Rumble is a game designed to show how ratios and rates are related to fractions and decimals.…”
Section: Methodsmentioning
confidence: 99%
“…The two digital games used in this study were carefully selected and recommended to the participating teachers for use in this study as they had been shown to have a positive impact on mathematical learning outcomes in previous empirical studies and employed game mechanics that mapped directly to learning objectives (Denham, ). Ratio Rumble is a game designed to show how ratios and rates are related to fractions and decimals.…”
Section: Methodsmentioning
confidence: 99%
“…The representations in a digital game come in a variety of forms including pictorial images, words, numbers and auditory features. Representations in a digital game have an important influence on children's mathematical outcomes (Castellar, All, de Marez, & Van Looy, 2015; Denham, 2015; Sedig, 2008; Siew, 2018). Research shows that when children make connections among different representations, this supports the development of their mathematical concept images because different mathematical representations can stand for the same mathematical idea (e.g., the word ‘triangle’ and an image of a triangle; Lesh, Post, & Behr, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…What may be more decisive is the instruction and support provided through the game. Denham () identifies a number of important features of more successful mathematics games: learning targets well aligned with the game's objectives and placed in an interesting context; the right level of challenge and difficulty alongside scaffolding that promotes reflection; timely feedback; and the game mechanic (the system of rules for interacting with the game) consistent with the instructional objective. These overlap with the key elements that Hirsh‐Pasek et al () identify for children at a young developmental age.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong case for the place of games in mathematics education. Games can produce high levels of motivation, and children benefit from well‐defined rules and clear goals (Denham, ). A fun environment can offset the tedium of repeated practice that can be characteristic of teaching children with DS (Moni & Jobling, ).…”
Section: Introductionmentioning
confidence: 99%